Relasi Dan Makna Cerita Fantastik Dalam Novel “Kisah Tanah Jawa ”Karya Mada Zidan. - Yazid, Muhammad Hikmal; Atikurrahman, Moh (CV. ITTC INDONESIA, 2023)
This study describes several stories in the mystical land of Java and are still a distinctive culture of people's lives during the colonial period in the Story of the Land of Java. The land of Java has many mystery stories that will not be finished overnight. Mysterious figures, mystical rituals and haunted places, always make us curious. This research uses the fantastic theory of Tzvetan Todorov and the important thing from what Todorov says is that the readers' doubts in the two camps of doubt are before the first condition in fantastical. This phenomenon can be felt by the reader in the two estuaries of imagination and reality.According to Djokosujatmo (2005) fantastic is a doubt that is felt by humans who only know natural law, when facing a phenomenon that looks supernatural in life. we can draw the conclusion that the work is able to show the existence of dominant fantastical stories from motifs, plots, themes, characters, space, time and realistic decor. All of these elements move towards a single element that unites a fantastic story that manifests its phenomena illogically and under the expectations of its readers.